Tingkat Engagement dan OCB Karyawan CV Panca Bina Banua Kecamatan Sungai Loban Kabupaten Tanah Bumbu - Anastasia Wahyu Trigunarti; Titien Agustina; Dodik Jatmika; Alfiannor Alfiannor (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
This study aims to analyze the level of employee engagement and organizational citizenship behavior (OCB) in CV Panca Bina Banua, located in the Sungai Loban district of Tanah Bumbu regency. Data was collected using a questionnaire administered to 32 randomly selected employees from the company's workforce. The results of the analysis indicate that the level of employee engagement in CV Panca Bina Banua falls into the moderate category, while the level of OCB is high. Furthermore, there is a significant relationship between employee engagement and OCB. The findings of this study are expected to provide insights to the management of the company on how to enhance employee engagement and OCB, which in turn can improve the overall performance of the company.